1999
DOI: 10.1128/mcb.19.7.4980
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 Is Tyrosine Phosphorylated in Response to Interleukin-2 and Suppresses STAT5 Phosphorylation and Lymphocyte Proliferation

Abstract: Members of the recently discovered SOCS/CIS/SSI family have been proposed as regulators of cytokine signaling, and while targets and mechanisms have been suggested for some family members, the precise role of these proteins remains to be defined. To date no SOCS proteins have been specifically implicated in interleukin-2 (IL-2) signaling in T cells. Here we report SOCS-3 expression in response to IL-2 in both T-cell lines and human peripheral blood lymphocytes. SOCS-3 protein was detectable as early as 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
194
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(205 citation statements)
references
References 35 publications
10
194
1
Order By: Relevance
“…Specifically, IL-2R signaling activates STAT5, but not protein kinase B/Akt, due to the constitutive expression of phosphatidylinositol-phosphatase, phosphatase and tensin homolog deleted on chromosome 10 (PTEN). Additionally, high levels of suppressor of cytokine signaling 3 (SOCS3) has been observed in Treg, which may dampen or modify the signal transduced by the IL-2R [5,[34][35][36]. Taken together, these data open the possibility that IL-2Rb generates a distinct signaling signature in Treg leading to Foxp3 transcription.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, IL-2R signaling activates STAT5, but not protein kinase B/Akt, due to the constitutive expression of phosphatidylinositol-phosphatase, phosphatase and tensin homolog deleted on chromosome 10 (PTEN). Additionally, high levels of suppressor of cytokine signaling 3 (SOCS3) has been observed in Treg, which may dampen or modify the signal transduced by the IL-2R [5,[34][35][36]. Taken together, these data open the possibility that IL-2Rb generates a distinct signaling signature in Treg leading to Foxp3 transcription.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we may suggest that these immune organs of carp are involved in cytokine (such as IL-12 and IFN-a/b) signalling induced by SVCV and require being regulated by SOCS-3, and then SOCS-3 acts as a negative-feedback loop to suppress these cytokine receptor signalling for balancing cytokine action. In addition, Wang et al found that trout SOCS-3 gene is higher expression induced by two cytokines in the monocyte/macrophage RTS-11 cell line than in fibroid RTG-2 cell line [18], and previous reports have also indicated that SOCS-3 is induced in T cells, B cells, neutrophils, macrophages and DCs by a variety of agents both in vitro and in vivo [3,7,42,43], which may explain why the induced expression of carp SOCS-3 gene was significantly up-regulated in the immune organs in this study. Noteworthily, in human, the inhibition of the IFN system by virus (HSV-1)-induced SOCS-3 can confer efficient viral replication, and SOCS-3 is up-regulated via activated STAT3 and it efficiently inhibits IFN-a/b signalling [38].…”
Section: Discussionmentioning
confidence: 96%
“…Since 1997 [5], numerous studies have identified that SOCS-3 acts as a negative-feedback inhibitor to suppress the cytokine receptor signalling, for example, in myeloid cells, SOCS-3 is a key negative regulator of G-CSF signalling [6]. It negatively regulates IL-2 signalling [7] and IL-2 production via CD28 signalling [8], inhibits IL-6 signalling in macrophages [9e11], and promotes Th2 development by inhibiting IL-12 mediated STAT4 activation in T cells [12]. The knocking down SOCS-3 gene in T helper cells reduced the immune responses, and resulted in the overexpression of IL-10 and transforming growth factor [13].…”
Section: Introductionmentioning
confidence: 99%
“…It can bind to both JAK1 and the IL2 receptor b chain, inhibit STAT 5 signalling and maintain activation of the ras/MAP kinase pathway by binding to RasGAP (Cacalano et al, 2001). In addition, SOCS-3 can suppress Epo signalling by associating with the Epo receptor and JAK2 (Cohney et al, 1999;Sasaki et al, 2000;Cacalano et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SOCS-3 is tyrosine phosphorylated following Epo, IL-2, epidermal growth factor and platelet-derived growth factor stimulation (Cohney et al, 1999;Cacalano et al, 2001). It can bind to both JAK1 and the IL2 receptor b chain, inhibit STAT 5 signalling and maintain activation of the ras/MAP kinase pathway by binding to RasGAP (Cacalano et al, 2001).…”
Section: Introductionmentioning
confidence: 99%